2005
DOI: 10.1007/s00198-004-1799-7
|View full text |Cite
|
Sign up to set email alerts
|

Fracture risk in patients with prostate cancer on androgen deprivation therapy

Abstract: Although a decrease in bone mass is a well-known side effect of hormone therapy for prostate carcinoma, its clinical significance is unclear, as there is only scanty information about the incidence of fractures. Therefore, the aim of this study was to determine the risk of non-metastatic fractures in patients with prostate cancer undergoing androgen deprivation therapy. We performed a retrospective cohort study that comprised 288 patients with cancer who were subjected to androgen deprivation therapy (ADT). Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
53
2
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 33 publications
4
53
2
2
Order By: Relevance
“…Prostate cancer has a high likelihood of metastases to bone, and is treated with androgen deprivation therapy, which may lead to bone loss, and these two factors in combination may explain why a sustained increase in risk of fractures was seen. Furthermore, localised prostate cancer may be associated with a prolonged survival [43] and thus a sustained risk of even late metastases to the skeleton and detrimental effects of long-term androgen deprivation therapy [1,44]. Dickman et al [45] reported an early and sustained increase in the risk of hip fractures in patients who underwent bilateral orchiectomy for prostate cancer, In our study the increase was seen later in the cause of the prostate cancer and this may be due to the fact that not all patients underwent orchiectomy or received androgen deprivation therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prostate cancer has a high likelihood of metastases to bone, and is treated with androgen deprivation therapy, which may lead to bone loss, and these two factors in combination may explain why a sustained increase in risk of fractures was seen. Furthermore, localised prostate cancer may be associated with a prolonged survival [43] and thus a sustained risk of even late metastases to the skeleton and detrimental effects of long-term androgen deprivation therapy [1,44]. Dickman et al [45] reported an early and sustained increase in the risk of hip fractures in patients who underwent bilateral orchiectomy for prostate cancer, In our study the increase was seen later in the cause of the prostate cancer and this may be due to the fact that not all patients underwent orchiectomy or received androgen deprivation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Most research has focused on prostate cancer, where a decreased bone mineral density (BMD) and an increased risk of fractures, mainly linked to the use of anti-androgen therapy (androgen deprivation therapy) has been demonstrated [1]. Other types of cancer have not been studies in detail.…”
mentioning
confidence: 99%
“…In prospective clinical trials, bone loss rates in ADT-treated men with prostate cancer have been reported to range from 0.6% to 9% per year. [5][6][7][8][9][10][11][12] Retrospective studies in these men report fracture rates of 2.7% per year, 13 20% at 10 years, 14 and 8 per 100 person-years at risk. 15,16 Prostate cancer patients who underwent bilateral orchiectomy had even higher fracture rates than age-matched controls during 15 years of follow-up: 40% vs 19% (P<0.001).…”
mentioning
confidence: 97%
“…Overall, only 14.7% of patients (95% CI = 9.5-20.0%) were treated to maintain physiological BMD. Oral and [15,17] . HCM = Hypercalcemia of malignancy .…”
Section: Biphosphonates Against Cancer Treatmentinduced Bone Lossmentioning
confidence: 99%
“…Androgen-deprivation therapy, either by bilateral orchiectomy or treatment with a gonadotropin-releasing hormone agonist (GnRH-A), has been found to further reduce BMD by 4-13% per year [1,[11][12][13][14] . ADT is associated with a fourfold increase in the incidence rate of both peripheral and vertebral fractures [15] . Continuous monitoring of BMD and preventive measures against bone loss are strongly recommended.…”
mentioning
confidence: 99%